Production Monitoring Based on Sensing Clamping Elements. (2016) - Denkena, Berend; Dahlmann, Dominik; Kiesner, Johann
Abstract: Clamping errors in workpiece positioning decrease the production outcome of machine tools by causing rejects. An automated monitoring of these failures does not take place in practice, due to limited installation space for the sensor integration, especially in series production. Within the Collaborative Research Centre 653, the IFW develops and investigates a condition and process monitoring system based on sensing clamping elements in close cooperation with two industrial partners, the companies Roemheld GmbH (clamping technology manufacturer) and ReiKam GmbH (fixture construction service provider). It consists of hydraulic clamping elements with integrated sensors, decentral electronics for signal preprocessing, bus communication and a central processing unit. Measureable quantities are hydraulic pressure, the clamping stroke and the process forces. This article describes the prototypical realization and shows its usability in condition and process monitoring. Experimental results from measurements during milling operations and the comparison with a dynamometer demonstrate the performance of the sensory clamping system.